Global trends in esophageal cancer: sex and age disparities in health inequalities from 1990 to 2021, with projections to 2050 - Liu, Ying; Wu, Erman; Cheng, Fang; Zhang, Meng; Rou, Qian; Nuertai, Zenati; Xu, Maorong; Xu, Shanshan; Li, Minghui; Zhang, Lei; Nasiroula, Aheli (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer remains one of the deadliest cancers globally, highlighting significant health challenges and socioeconomic disparities. This study aims to measure its global burden, assess disparities by sex, age, and region, and evaluate health inequalities, with projections to 2050. The goal is to provide evidence to guide resource allocation and reduce the disease burden.MethodsUsing data from the Global Burden of Disease (GBD) 2021 study, we analyzed trends in prevalence, incidence, mortality, and Disability-Adjusted Life Years (DALYs) across sexes, age groups, and 204 countries and territories. Age-standardized rates (ASR) were calculated to account for population age structures. Trends over time were assessed using the estimated annual percentage change (EAPC). Health inequalities were evaluated using the Slope Index of Inequality (SII) and Concentration Index (CI). Future burdens were projected using Bayesian Age-Period-Cohort (BAPC) models.ResultsFrom 1990 to 2021, esophageal cancer cases increased: prevalence from 551.62 to 1004.2 thousand, incidence from 354.73 to 576.53 thousand, mortality from 356.26 to 538.6 thousand, and DALYs from 9753.57 to 12999.26 thousand. However, age-standardized rates declined: prevalence from 13.34 to 11.47, incidence from 8.86 to 6.65, mortality from 9.02 to 6.25, and DALYs from 235.32 to 148.56 per 100,000 people. The burden rises sharply after age 40, with males and low-SDI regions experiencing higher burdens. Health inequalities widened, with the SII for prevalence increasing from 2.52 to 5.67, and for deaths from 1.45 to 2.94. West Africa, North Europe, and North America saw rising prevalence rates, while East Asia showed a declining trend. A decreasing trend is observed in most countries and regions worldwide, particularly in East Asia, with projections suggesting a continued decline in the future.ConclusionAlthough projections indicate a decreasing trend, health inequalities have intensified. Regions such as West Africa, North Europe, and North America are experiencing rising prevalence. To address these disparities, targeted interventions, enhanced healthcare access, and preventive measures in high-burden areas are essential to reduce the global burden and advance health equity.